Toward a visuospatial developmental account of sequence-space synesthesia - Price, Mark; Pearson, David (Frontiers in Human Neuroscience, 2013)
Sequence-space synaesthetes experience some sequences (e.g. numbers, calendar units) as arranged in spatial forms, i.e., spatial patterns in their mind’s eye or even outside their body. Various explanations have been offered for this phenomenon. Here we argue that these spatial forms are continuous with, and share central characteristics with, varieties of non-synaesthetic visuospatial imagery. This includes their dynamic and elaborative nature, their involuntary feel and consistency over time. Drawing from literatures on mental imagery and working memory, we suggest how the initial acquisition and subsequent elaboration of spatial forms could be accounted for in terms of the known developmental trajectory of visuospatial representations. This extends from the formation of image-based representations of verbal material in childhood to the later maturation of dynamic control of imagery. Individual differences in the development of visuospatial style also account for variation in the character of spatial forms, e.g. in terms of distinctions such as visual versus spatial imagery, or ego-centric versus object-based transformations.